Assessing the Feasibility of Markerless Close Range Photogrammetry in Industrial Inspection: A Foundational Study - I. Prieto; P. Puerto; I. Leizea; I. Herrera (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
As large-volume metrology gains significance in industrial applications, ensuring high-accuracy measurements (±0.1 mm) with cost-effective and user-friendly technologies becomes increasingly challenging. This study evaluates the performance of Markerless Photogrammetry (MP) against industry standards such as Coordinate Measuring Machines (CMM), Laser Trackers (LT), and Marker-based Photogrammetry (MbP) to identify the potential of MP in addressing industrial challenges. While CMM and LT offer high accuracy, their applicability is limited by the size of large workpieces and cost. MbP offers high work ranges, flexibility and ease of use, but it is restricted to sparse measurements and lacks the accuracy of traditional methods. Despite its lower accuracy, the results indicate that MP may present a viable solution for cases where cost-effectiveness and ease of use are crucial with the drawback of high computational cost.